A System Justification Theory of Entrepreneurial Attitudinal Change During a Crisis. (May 2023) - Liu, Kun; Fu, Kun; Yang, Jing Yu; Al Asady, Ahmad
Entrepreneurship resilience during a crisis is an important research area. However, prior research has not examined cognitive antecedents of entrepreneurial resilience. Using the 2014 oil price crisis in the Middle East as a natural experiment, we draw on system justification theory to understand why and how entrepreneurs differ in the extent of their attitudinal changes toward corruption. We find foreign entrepreneurs substantially increased their willingness to engage in corruption whereas local entrepreneurs did not. Among foreign entrepreneurs, corruption willingness increases more among those from countries where corruption is not the norm, than those from more corrupt home countries.